Motivasi Menabung Pada Remaja Masjid Hifzul Amanah, Jakarta - Andri Faisal; Dade Maulana Machdun (Jurnal Pengabdian Kepada Masyarakat Kalam, 2022)
This community service activity aims to socialize saving in the community. This is based on the low interest in saving for the Indonesian people. With a minimum of saving, welfare will be difficult to fulfill and will cause them to become poor. To socialize the most appropriate is to young people or children. Inculcating the habit from an early age will make them accustomed to saving tomorrow. The findings found that the participants had not saved and it turned out that their parents did not play a role in this either